বানান-অভিধান ও বাংলা বানানের নিয়ম - সিকদার, সৌরভ (ঢাকা : অনন্যা প্রকাশনী, 1999)
Dictionary of, and rules for spelling Bengali words.
"বাংলা একাডেমী প্রমিত বাংলা বানানের নিয়ম অনুসারে"
Includes bibliographical references (p. 381-[382]).
In Bengali.
Keywords: Bengali language -- Orthography and spelling -- Dictionaries; Bengali language -- Orthography and spelling